2015
DOI: 10.5194/nhessd-3-3409-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can an early warning system help minimize the impacts of coastal storms? A case study of the 2012 Halloween storm, Northern Italy

Abstract: Abstract. The Emilia-Romagna Early Warning System (ER-EWS) is a state-of-the-art coastal forecasting system that comprises a series of numerical models (COSMO, ROMS, SWAN and XBeach) to obtain a daily three-day forecast of coastal storm hazard at eight key sites along the Emilia-Romagna coastline (Northern Italy). On the night of 31 October 2012, a major storm event occurred that resulted in elevated water levels (equivalent to a 1-in-20 to 1-in-50-year event) and widespread erosion and flooding. Since this st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The previous maximum value recorded by this station was 1.16 m on October 31, 2012, during another storm event (Harley et al . , ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The previous maximum value recorded by this station was 1.16 m on October 31, 2012, during another storm event (Harley et al . , ).…”
Section: Resultsmentioning
confidence: 97%
“…, ; Harley et al . , ). In this context, the objective of this study is to investigate the shallow coastal aquifer response to exceptional storm events that brought to unexperienced flooding conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The hazard maps were qualitatively validated through the comparison with floods and damages measured after the 31 October-1 November 2012 storm (Harley et al, 2015), which was characterised by very high surge levels (1.15 m a.m.s.l., measured at Porto Corsini tide gauge, Ravenna, Fig. 1), between a 1-in-20-and a 1-in-50-year return period event and a significant wave height of 2.41 m (measured at the Cesenatico buoy, Fig.…”
Section: Lido DI Classe-lido Di Savio-cervia Sitesmentioning
confidence: 99%
“…In the Results section of the current paper, the comparison with a recent storm (10 March 2010) is presented as a validation exercise. A second validation was carried out after a strong event occurred during the night of 31 October-1 November 2012, locally known as the "Halloween storm" (Harley et al, 2015).…”
Section: Vulnerability Maps Along Profile Linesmentioning
confidence: 99%
“…Studies have shown XBeach to effectively hindcast storm impact, overwash and breaching on sandy beaches [30,31]. It has also been used in the operation of coastal impact forecasting systems to forecast when storm impact hazard thresholds are exceeded by hydrodynamic and wave conditions [44,45]. As the beach at Rhyl is composed of sand and a fixed sea wall, XBeach is a suitable model to use for this study as it can represent the variable and fixed evolution of the beach and sea wall, respectively.…”
Section: Modelling Approachmentioning
confidence: 99%